Integration of Social Emotional Learning and Problem-Based Learning in Elementary School Social Studies Education: A Systematic Literature Review (2020-2025) - Rita Ninda Agustin; Muh Sholeh; Bambang Subali; Nuni Widiarti (Papanda Publisher, 2026)
The integration of Problem-Based Learning (PBL) and Social Emotional Learning (SEL) has been increasingly promoted to support both academic achievement and character development in primary education. However, systematic evidence on the application of SEL-based PBL in elementary social studies learning remains limited. This study aims to review research trends and empirical findings on the implementation of SEL-based PBL in elementary schools from 2020 to 2025. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Data were collected from Scopus, SINTA, ScienceDirect, and Publish or Perish (PoP) databases. From 103,090 identified records, 33 articles met the inclusion criteria and were analyzed using bibliometric and content analysis supported by VOSviewer.The findings indicate that SEL-based PBL consistently improves students’ social-emotional skills, emotional intelligence, character, collaboration, learning motivation, and academic outcomes. Bibliometric mapping shows a growing focus on 21st-century skills and emotional regulation since 2022. However, this review reveals research gaps, particularly the limited focus on social studies, the use of small samples and non-standardized SEL instruments, and the lack of studies on digital or hybrid SEL-based PBL models. Further rigorous and large-scale studies are therefore needed to strengthen the empirical foundation of this approach.